THE GAME FOR REGIONAL HEGEMONY: CHINA’S OBOR AND INDIA’S STRATEGIC RESPONSE - Rahul, Dr. Anshuman (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
The OBOR initiative of China often termed as ‘Modern-day Silk Road’ is based on President Xi Jinping’s epic vision to make ‘China Great Again’ by reviving the Silk Route of ancient times. This initiative aims to engage Eurasia economically by creating a network of infrastructure. In this regard, the article attempts to understand the geo-politics behind India’s refusal to join OBOR and strategic response to counter the most appealing economic engagement of the present era but considered to be a debt-trap by India.